2012
DOI: 10.1017/s1368980012003606
|View full text |Cite
|
Sign up to set email alerts
|

Survey of nutrition knowledge of physicians in Kuwait

Abstract: Objective: The objective of the present study was to determine whether nutrition knowledge differs between male and female physicians working in Kuwait City, Kuwait. Design: The study employed a cross-sectional analysis of physician's nutrition knowledge by using a sixteen-item multiple-choice questionnaire. Setting: Governmental hospitals in Kuwait City, Kuwait. Subjects: One hundred Kuwaiti physicians (fifty males; fifty females) working in Kuwait City, Kuwait. Results: A response rate of 73 % was achieved (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 10 publications
6
19
3
Order By: Relevance
“…In Kuwait, it was reported that physicians provided inaccurate nutrition information related to common health problems such as obesity, hypertension and osteoporosis. It has been suggested that a nutrition course should be introduced into medical education at universities, as well as refreshment training courses for physicians [21]. Given the lack of nutrition information among university students and physicians, there is a need to implement educational nutrition programmes in Kuwait and other Arab countries, either through the mass media or school and university curricula.…”
Section: Discussionmentioning
confidence: 99%
“…In Kuwait, it was reported that physicians provided inaccurate nutrition information related to common health problems such as obesity, hypertension and osteoporosis. It has been suggested that a nutrition course should be introduced into medical education at universities, as well as refreshment training courses for physicians [21]. Given the lack of nutrition information among university students and physicians, there is a need to implement educational nutrition programmes in Kuwait and other Arab countries, either through the mass media or school and university curricula.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the questionnaire was done in a multiphasic process. In the first phase, a thorough review of the literature was conducted to identify the questionnaires and modalities that have been used in the Middle East [9][10][11][12][13][14][15][16]. The items in these questionnaires were then checked for their suitability and adaption by an experienced dietician and a public health researcher (NS & AW) inclusion in the Kuwaiti Diet & Nutrition Scale.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is crucial for medical professionals to have an adequate level of nutrition in order to improve patient outcomes [4]. Unfortunately, several investigations have shown poor knowledge of nutrition among medical professionals, partly owing to their deficient education during preclinical and clinical training [5][6][7]. It is, therefore, imperative that nutrition knowledge of practicing medical professionals be assessed to overcome gaps in knowledge and improve patient care [8].…”
Section: Introductionmentioning
confidence: 99%
“…The development of the questionnaire was done in a multiphasic process. In the first phase, a thorough review of the literature was conducted to identify the questionnaires and modalities that have been used in the Middle East [9][10][11][12][13][14][15][16]. The items in these questionnaires were then checked for their suitability and adaptation by an experienced dietician and a public health researcher (NS & AW) inclusion in the ATNQ.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…Therefore, it is crucial for medical professionals to have an adequate knowledge of nutrition in order to improve patient outcomes [4]. Unfortunately, several investigations have shown poor knowledge of nutrition among medical professionals, partly owing to their deficient education during preclinical and clinical training [5][6][7]. It is, therefore, imperative that nutrition knowledge of practicing medical professionals be assessed to overcome gaps in knowledge and improve patient care [8].…”
Section: Introductionmentioning
confidence: 99%